Female Ulamā and Religious Moderation in Indonesia: A Study on the Agency and Authority of KUPI and JP3M - Nadia, Zunly; Faizah, Nur (UIN Sunan Kalijaga Yogyakarta, 2024)
The term ulamā is not exclusively associated with men but also includes women. However, despite the recognition of female ulamā, male ulamā continue to dominate public perception in Indonesian Muslim society, particularly in the realm of fatwās. As a result, the significant contributions of female ulamā remain largely undocumented in the historical development of Islam in Indonesia. Given the extensive yet often overlooked role of female ulamā, the establishment of the Indonesian Congress of Female Ulamā (Kongres Ulama Perempuan Indonesia, KUPI) and the Association of Female Islamic Boarding School Leaders and Preachers (Jam’iyah Perempuan Pengasuh Pesantren dan Muballighah, JP3M) marks a significant development. These two institutions serve as platforms for female ulamā to convene and assert their influence through various scholarly and social activities. This study uses a qualitative research approach, with data presented in a descriptive narrative format. A qualitative approach is chosen to enable an in-depth exploration of the role of KUPI and JP3M female ulamā in promoting religious moderation in Indonesia. This approach enables a contextual analysis of both the subjects and objects of study, preventing the risk of overgeneralization of the observed phenomena.